Perceived negative activities: understanding the Nexus and mind set in our societies - OBAGBINOKO, Clement Odiri; ORHERO, Abraham Ejogba; EFEBEH, Vincent Eseoghene (International Journal of Psychosocial Rehabilitation, 2020)
As the twin phenomena of organized crime and terrorism continue to threaten global peace, the search for effective ways of dealing with them has continued to engage the attention of scholars in the field of conflict and conflict resolutions. The paper identifies and discusses the distinguishing and common features of organized crime and terrorism and the factors that engender these two lives and peace threatening phenomena. Essentially, the paper identifies the social movement and deprivation theories as to the basis of the rising incidence of organized crime and terrorism and the pervasive and profound role politics and religion play in determining the activities and membership of organized crime and terrorism. Also, the paper identifies the three categories of persons who are potential members of organized crime and terrorism and the factor of their mind-set as a motivating factor. The paper thinks that despite the features that distinguish organized crime from terrorism, there exists a point of convergence between the two phenomena in their modus operandi.